BIROKRASI BERINTEGRITAS: FONDASI MENUJU TATA KELOLA PEMERINTAHAN BERSIH - Fanila Kasmita Kusuma (Media Bina Ilmiah, 2024)
Clean governance is a fundamental prerequisite for establishing a democratic, accountable, and citizen-oriented state. However, the greatest challenge in achieving this lies in the weak integrity of the bureaucracy, often manifested through corruption, nepotism, and abuse of power. This study aims to analyze the role of integrity as the main foundation for building a bureaucracy that supports clean and effective governance. The research employs a qualitative approach through a literature review of policy documents, previous studies, and comparative analysis of governance practices in several countries. The findings reveal that a bureaucracy that upholds integrity significantly enhances transparency, accountability, and public trust in government institutions. Key strategies that must be implemented include merit-based recruitment reform, the strengthening of ethical leadership, and the application of transparent digital oversight systems. The study concludes that the success of clean governance heavily depends on the commitment to establishing integrity at all levels of bureaucracy. These findings offer strategic recommendations for policymakers and stakeholders to reinforce the integrity pillar as a pathway to clean and competitive governance